Opioid analgesics for chronic noncancer pain in patients prescribed opioid agonist therapy or with opioid use disorder: A systematic review - Vahid Ashoorion; Tushar Sood; Shezel Muneer; Jason W. Busse; Danielle Rice; Jaris Swidrovich; Umair Majid; James Abesteh; Randi Q. Mao; Abhimanyu Sud (Canadian Journal of Pain, 2025)
Background Opioid use disorder (OUD) is a growing public health concern in North America, often coexisting with chronic noncancer pain (CNCP). Managing both conditions presents unique challenges, highlighting the need for evidence to guide decision making.Aim The study aimed to conduct a systematic review that summarizes evidence on the efficacy, effectiveness, and safety of opioid analgesics alone or in combination with opioid agonist therapy (OAT) to manage CNCP in people with OUD or with a history of OUD.Methods We searched MEDLINE, Embase, PsycINFO, CINAHL and AMED from inception to July 2023 for randomized studies and up to January 2025 for non-randomized studies that explored the efficacy, effectiveness, and safety of opioids for people living with chronic pain and current or prior OUD. We assessed the risk of bias in included studies, evaluated the quality of evidence using the GRADE approach, and provided a narrative summary of treatment effects.Results Our search identified 15,988 unique citations, of which six observational studies were deemed eligible to inform safety outcomes for review, while no observational studies or RCTs met the eligibility criteria for efficacy or effectiveness outcomes. The likelihood of suicidality was twice as high in CNCP patients with OUD receiving long-term opioid analgesics compared to those without OUD (absolute risk increase: 127; 95% CI: 36 to 249 more participants with suicidality in 1,000 participants; moderate certainty evidence). Compared to opioid analgesics alone, the risk of fatal opioid-related overdose may decrease in patients with CNCP and OUD who receive both opioid analgesics and OAT (absolute risk reduction: 60; 95%CI: 18 to 94 fewer deaths in 1,000 participants; low certainty evidence).Conclusions There is a paucity of evidence to inform practice and policy regarding opioid analgesic prescribing amongst people with OUD. Existing evidence suggests that such prescribing is associated with a higher risk of suicidality, while the use of OAT together with opioid analgesics in this population may be protective against fatal overdose. Further observational and trial research is needed to clarify the benefits and harms of opioid analgesics for CNCP patients with OUD.